2018
DOI: 10.1186/s13568-018-0677-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Substrates specificity of tannase from Streptomyces sviceus and Lactobacillus plantarum

Abstract: Tannases can catalyze the hydrolysis of galloyl ester and depside bonds of hydrolysable tannins to release gallic acid and glucose, but tannases from different species have different substrate specificities. Our prior studies found that tannase from Lactobacillus plantarum (LP-tan) performed a higher esterase activity, while the tannase from Streptomyces sviceus (SS-tan) performed a higher depsidase activity; but the molecular mechanism is not elucidated. Based on the crystal structure of LP-tan and the amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Substrate specificities of tannases from different organisms are quite different [ 18 ]. The gallotannin-decomposing tannases include two separate enzymes, an esterase and a depsidase, with specificities for methyl gallate and m-digallic acid ester linkages, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrate specificities of tannases from different organisms are quite different [ 18 ]. The gallotannin-decomposing tannases include two separate enzymes, an esterase and a depsidase, with specificities for methyl gallate and m-digallic acid ester linkages, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gallotannin-decomposing tannases include two separate enzymes, an esterase and a depsidase, with specificities for methyl gallate and m-digallic acid ester linkages, respectively [ 19 ]. The tannase of Lactobacillus plantorum displays a higher esterase activity, while the tannase from Streptomyces sviceus exhibits a higher depsidase activity [ 18 ]. Tan Hcw from H. camelliae hydrolyzes EGCG and ECG much effectively than MG, which suggests that Tan Hcw may favorable to be a depsidase.…”
Section: Discussionmentioning
confidence: 99%
“…The Editor-in-Chief has retracted this article (Wang et al 2018) because the authors do not have ownership of the data they report. An investigation by the Commonwealth Scientific and Industrial Research Organisation (CSIRO) has concluded that the data reported in this article are the sole property of the CSIRO.…”
Section: Retraction To: Amb Expr (2018) 8:147 101186/s13568-018-0677-1mentioning
confidence: 99%